Turning uncertainty into opportunity: a new way to use-the-future - Martin Calnan; Christine Kavazanjian; Amos Taylor; Noora Vähäkari (Medium, 2026)
Rather than forecasting and planning for a limited set of possible scenarios and retrofitting our solutions to them, why not take a different approach: turn uncertainty and complexity into assets and opportunities that enable innovation, leadership, discovery, choice, knowledge, and more.